In utero testosterone exposure influences physiological responses to dyadic interactions in neurotypical adults. Issue 5 (8th April 2016) - Truzzi, Anna; Senese, Vincenzo Paolo; Setoh, Peipei; Ripoli, Cristian; Esposito, Gianluca
Abstract : Objective: We investigated how different levels of prenatal exposure to testosterone influence physiological reactions to dyadic interactions, hypothesising that higher levels of prenatal testosterone are linked to greater physiological responses. Method: Autonomic nervous system responses to dyadic interactions focussed on social or physical norms were measured. Physiological assessment of excitability (heart rate, facial temperature) and a behavioural assessment (Likert items judgements) were run on 25 neurotypical participants who had distinct testosterone exposure levels in utero . In utero exposure to testosterone was assessed measuring 2D : 4D (ratio between the lengths of the index and the ring fingers). Results: Higher testosterone exposure participants showed greater physiological arousal: a greater heart rate decrease, independent from scenario type ( p <0.05), and opposite facial temperature changes in response to social (increase) (vs.) physical scenarios (decrease) were found (Left-cheek: p <0.05; Right-cheek: p <0.05). Conclusion: These findings suggest a long-term influence of prenatal environment on adults' physiological responses during social situations.